The McGurk Universe - Donnelly, K.J. author. aut Link
IX, 221 p. 36 illus., 20 illus. in color.
Keywords: This book reconsiders audiovisual culture through a focus on human perception, with recourse to ideas derived from recent neuroscience. It proceeds from the assumption that rather than simply working on a straightforward cognitive level audiovisual culture also functions more fundamentally on a physiological level, directly exploiting precise aspects of human perception. Vision and hearing are unified in a merged signal in the brain through being processed in the same areas. This is illustrated by the startling ‘McGurk Effect’, whereby the perception of spoken sound is changed by its accompanying image, and counterpart effects which demonstrate that what we see is affected by different sounds accompanying sounds. This blending of sound and images into a whole has become a universal aspect of culture, not only evident in films and television but also in video games and short Internet clips. Indeed, this aesthetic formation has become the dominant of this period. The McGurk Universe attends to how audiovisual culture engages with and mediates between physiological and psychological levels. K.J. Donnelly is Professor of Film and Film Music at the University of Southampton, UK, and author of The Shining (2017), Magical Musical Tour (2015), Occult Aesthetics (2013), British Film Music and Film Musicals (2007), The Spectre of Sound (2005), and Pop Music in British Cinema (2001).